ANALISIS DAMPAK ALIH FUNGSI LAHAN SAWAH TEHADAP KETERSEDIAAN BERAS DI KOTA SERANG - Muhtadi, Muhamad; Meutia, Meutia; Saleh, Khaerul (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2021)
The impact of the conversion of rice fields on rice food durability can be seen from the availability of rice produced by rice compared to the rice consumption needs of the population. The availability of rice is obtained by converting the amount of production in the form of dry rice (GKP) into rice, while the population's rice consumption needs are calculated using the approach of Recommended Dietary Allowance (RDA). The results of the study show that the population projection of Serang City in 2026, the total rate of conversion of rice fields for the last 5 years in Serang City is -4.64 percent or has decreased by around 387 Ha. The conversion of rice fields in Serang City has a negative impact on availability of rice. As a result of the conversion of rice fields, Serang City experienced a loss of rice production of 3785.46 tons and it is predicted that Serang City in 2026 will experience a shortage of 78,324 tons of rice to supply the food needs of the residents of Serang City if the Serang City government does not take action to reduce the rate of land conversion. and the rate of population growth. To supply the food needs of Serang City in the next 5 years, Serang City needs an area of 22,806 hectares of rice fields to supply the food needs of Serang City of 185,092 tons of GKP in 2026. It is predicted that Serang City will experience a shortage of 15,370 hectares of rice fields if the government does not take action. to control the conversion of rice fields and the population growth of Serang City.